Compliance Risk Analysis in the Internal Supervision by Government Internal Supervisory Apparatus (APIP) - Yulya Handayani; Noer Azam Achsani; Ferry Ardiansyah (Politeknik Ganesha Medan, 2025)
This study aims to identify compliance risks within internal supervision activities, analyze the root causes, and formulate effective mitigation strategies. The research was conducted on the Government Internal Supervisory Apparatus (APIP) at Ministry X. The sampling technique used was purposive sampling, with a sample size of 5 key informants responsible for internal supervision. The method employed was a qualitative approach with a case study design. Descriptive analysis was supported by primary data obtained through in-depth interviews and Focus Group Discussions (FGD). The main findings of this study indicate that non-compliance with audit procedures, financial statement reviews, and budget plan reviews is primarily caused by disproportionate workloads, time constraints, and inadequate resource allocation. The impact of this non-compliance includes a decline in the quality of supervision outcomes and the institution's credibility. The conclusion of this study underscores the importance of implementing comprehensive mitigation strategies, including setting priorities within work procedures, forming teams that are competent and appropriately matched to the workload, and enhancing coordination among supervisory units. The implementation of these strategies is expected to improve compliance with work procedures and enhance the quality of internal supervision in the public sector.